Capsaicin in Pain Management A Spicy Solution to Chronic and Neuropathic Pain - Konrad Pilarski; Adam Kucharski; Rafał Makuch; Alicja Chrościcka; Kamil Gała; Andrzej Czajka; Paweł Lenard; Sara Michalska; Martyna Dewicka; Alicja Maria Wawrzyniak (Quality in Sport, 2024)
Introduction and purpose: